2019
DOI: 10.18203/2394-6040.ijcmph20192609
|View full text |Cite
|
Sign up to set email alerts
|

Screening for diabetes using Indian diabetic risk score in the field practice area of tertiary care hospital, Maharashtra

Abstract: Background: Globally, people living with diabetes were estimated to be 422 million in year 2014. In India, an estimated 7.8% have diabetes. Early detection and prompt treatment for diabetes is key to achieve sustained control and prevent complications. The Indian diabetic risk score (IDRS) is one of simple screening tool to find the risk for diabetes in the community of filed practice area of teaching hospital.Methods: A community based cross sectional study was conducted in urban and rural field practice area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
3
1
1
Order By: Relevance
“…(9) In a study conducted by Ashturkar MD et al, 25% had low risk, 47.58% had moderate risk and 27.42% had a low risk for developing diabetes mellitus. (11) The findings of the above three studies are similar to our study.…”
Section: Resultssupporting
confidence: 90%
“…(9) In a study conducted by Ashturkar MD et al, 25% had low risk, 47.58% had moderate risk and 27.42% had a low risk for developing diabetes mellitus. (11) The findings of the above three studies are similar to our study.…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, similar findings of high risk were also reported in a study done by Chowdhury et al ., where 31.5% had high risk, and 22.5% had low risk but our study had lesser participants at low risk compared to both the studies followed by high risk. [ 3 6 ] Female participants had higher risk of developing diabetes which is similar to a study done by Dugg P et al . [ 7 ]…”
Section: Discussionsupporting
confidence: 77%
“…who found that 27.42%, 47.58% and 25% of the participants were in high, moderate and low risk respectively. [ 3 ] Here, moderate risk individuals are higher than the high-risk individuals as in this present study. On the other hand, similar findings of high risk were also reported in a study done by Chowdhury et al ., where 31.5% had high risk, and 22.5% had low risk but our study had lesser participants at low risk compared to both the studies followed by high risk.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations